Cybercrime Bill Entrenches Censorship, Surveillance (Human Rights Watch, 2026)
The Chinese government’s proposed law to combat cybercrime extends far beyond addressing legitimate legal concerns and contains sweeping provisions that pose a significant threat to human rights.